Unleashing Minds: Innovative Strategies to Foster Critical Thinking Skills in EFL Learners (Siddhajyoti Interdisciplinary Journal, 2025)
The landscape of English language teaching has evolved, focusing on developing critical and creative thinking skills among learners and educators. Despite numerous efforts, no single method has emerged as universally superior for fostering critical thinking, though some strategies prove more effective. This study examines instructional strategies that enhance critical thinking in EFL/ESL classrooms using document analysis. Strategies investigated include explicit instruction, teacher questioning, group discussions, reciprocal peer questioning, case-based learning, Socratic seminars, project-based learning, metacognitive strategies, problem-based learning (PBL), debate, reflective journals, inquiry-based learning, visual thinking strategies, role-playing, and collaborative problem-solving. Findings highlight explicit instruction as particularly effective, improving students' metacognition and analytical skills. Teacher questioning techniques engage students in deeper analysis and inference, while group discussions and peer questioning facilitate collaborative critical analysis. PBL and debate further enhance problem-solving and reasoning abilities. Reflective journals and inquiry-based learning promote self-reflection and analytical thinking. Acknowledging instructional variability as a limitation, this study suggests integrating these strategies into teacher training and curriculum development. This research suggests that diverse critical thinking strategies can enrich EFL/ESL learning environments and foster essential skills for complex problem-solving.